(untitled) (Filološke pripombe, 2019)
The external shape of the stone within the ethnological-anthropological observations, play probably the most important role his experience as "holy". The hole in this context that emerges as the main identification feature of sacred stones is an interesting aspect of many semantic messages that in itself brings. It is a symbolic element that reflects the cult-magical content in the eyes of the individual, and beyond the traditional community where it exists.